Mentoring Kristen sebagai Strategi Pendampingan Holistis bagi Mahasiswa Baru: Studi Kualitatif pada Domain Spiritual, Intelektual, Emosional, dan Sosial - Ganda Sari (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2026)
This study aims to explore the effectiveness of Christian mentoring practices in supporting new students' holistic adjustment across the spiritual, intellectual, emotional, and social domains. The study used a qualitative approach with six randomly selected new students from the class of 2024 at a Christian higher education institution in Tangerang who participated in a mentoring program for one academic year. Data sources included mentee interviews as primary data, mentoring program evaluations, and focus group discussions (FGDs) as supporting data. Data were analyzed using the Miles and Huberman (2014) model through the stages of data collection, data reduction, data presentation, and conclusion drawing. The evaluation results showed that this mentoring activity effectively supported students' holistic adjustment across four domains. In the intellectual domain, namely receiving intellectual support and learning strategies through mentors. In the emotional domain, namely acceptance without judgment and support for emotional regulation. And in the social domain, namely social adaptation and a sense of belonging. Meanwhile, the supporting data support the interview findings. However, there are some points that Christian higher education institutions should pay attention to, including the difficulty of finding a suitable time for mentoring meetings, the lack of normative mentoring activities, mentees becoming dependent on mentors and being treated unfairly, and the difficulty of building close relationships due to mentees being less active in asking questions or being shy. These points will serve as input for mentoring providers in Christian higher education.AbstrakPenelitian ini bertujuan mengeksplorasi efektivitas praktik mentoring Kristen dalam mendukung penyesuaian diri mahasiswa baru secara holistis pada domain spiritual, intelektual, emosional, dan sosial. Penelitian menggunakan pendekatan kualitatif dengan dengan subjek 6 mahasiswa baru angkatan 2024 disalah satu pendidikan tinggi Kristen di Tangerang yang mengikuti program mentoring selama satu tahun akademik yang dipilih secara acak. Sumber data meliputi wawancara mentee sebagai data utama dan evaluasi program mentoring dan FGD sebagai data pendukung. Data dianalisis menggunakan model Miles dan Huberman (2014) melalui tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil evaluasi menunjukkan bahwa kegiatan mentoring ini efektif mendukung penyesuaian diri mahasiswa secara holistis pada 4 domain. Pada domain intelektual, yaitu mendapatkan dukungan intelektual dan strategi belajar melalui mentor. Pada domain emosional yaitu penerimaan tanpa dihakimi dan dukungan regulasi emosi. Dan pada domain sosial yaitu adaptasi sosial dan rasa memiliki. Sedang pada data pendukung menyatakan dukungan terhadap temuan wawancara. Namun terdapat catatan yang harus diperhatikan oleh intitusi pendidikan tinggi Kristen, diantaranya adalah sulit menemukan waktu yang cocok untuk pertemuan mentoring, kegiatan mentoring bersifat normatif, mentee menjadi bergantung kepada mentor dan mentee yang diperlakukan tidak adil dan mentee masih sulit membangun kedekatan karena mentee kurang aktif bertanya atau malu. Masukan untuk institusi pendidikan Kristen.